Effects of Different Cooling Processes on the Structure and Properties of Aluminum/Steel Composite Plate - Yufei Zhu; Runwu Jiang; Chao Yu; Yuhua Wu; Hong Xiao (Chinese Journal of Mechanical Engineering, 2025)
Abstract The aluminum (Al)/steel transition joints used in ships are processed from composite plates, and their mechanical properties have a significant impact on the safety of ships. In this paper, the Al/steel composite plate was prepared using rolling, with 5083 aluminum plate as the cladding plate, Q235 steel plate as the substrate, and TA1 titanium (Ti) plate and DT4 pure iron (Fe) plate as the intermediate layers. The heterothermic billet was prepared through induction heating by the magnetic effects of the steel plate and the pure Fe plate, and then the Al/steel composite plate was obtained by rolling. The impacts of post-rolling cooling process on the microstructure and properties of the Al/Ti/pure Fe/steel composite plate were studied. The results manifested that the pure Fe/steel interface had a good composite effect. With the increase in the cooling rate, the bonding strength of the Al/Ti interface was raised, and that of the Ti/Fe interface was increased first and then decreased. When the oil cooling process was adopted, the Al/Ti/pure Fe/steel composite plate exhibited the highest comprehensive performance. The shear strength of the Al/Ti interface and the Ti/Fe interface was 102 MPa and 186 MPa, respectively. The plastic fracture was determined as the mode of interface fracture.